2019
DOI: 10.1002/fsn3.1114
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of vitreous and floury endosperm flours in maize

Abstract: Three maize cultivars with different endosperm types (flint, semiflint, and dent maize cultivars) were studied to characterize vitreous endosperm flour properties compared with those of floury endosperm flour from the same maize kernels. Vitreous endosperm flour had higher amylose and protein contents, and lower starch content, higher percentage of large starch granule, bigger mean diameter of starch granule, higher iodine capacity, higher trough viscosity and final viscosity and setback, lower swelling power,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…This effect was associated with a faster swelling of the starch granules in PHS flours due to floury endosperm. This result was in agreement with the findings of Zhang [ 45 ] who reported that floury endosperm flour showed higher swelling ability.…”
Section: Resultssupporting
confidence: 94%
“…This effect was associated with a faster swelling of the starch granules in PHS flours due to floury endosperm. This result was in agreement with the findings of Zhang [ 45 ] who reported that floury endosperm flour showed higher swelling ability.…”
Section: Resultssupporting
confidence: 94%
“…During cooling, YCG achieved a higher FV than APM, resulting in a higher degree of retrogradation. Some researchers, Singh et al 39 and Zhang and Xu, 40 associated these behaviors with the endosperm morphology of raw materials. Floury endosperm flours such as APM have greater ease of hydration during heating than YCG because their starch granules are surrounded by a smaller number of protein matrices, which act as physical barriers for water migration toward the granule.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary assessment by means of food frequency questionnaires is prone to error, and the glucosinolate content of the cruciferous vegetables consumed varies with variety, season, storage, and cooking methods. The development of reliable and accurate analytical techniques, including the 1,2benzenedithiol-based cyclocondensation assay [73] and improved HPLC-mass spectrometry methods for isothiocyanate [74] and indole derivatives, [75] has greatly facilitated the detection and quantification of isothiocyanates and indoles in foods, plasma, and urine. The use of urinary markers to measure dietary exposure to cruciferous vegetables is a potentially valuable advance.…”
Section: Discussionmentioning
confidence: 99%